The colorful facade decorations of the secession style in Sofia. Sofia mineral baths and the recovering of missing elements - Ivanova, Blagovesta (Facta Universitatis. Series: Architecture and Civil Engineering, 2024)
The report presents the national specific of the Secession style in the colourful ceramic decoration of some buildings in Sofia. The most representative between them are the church of St ?Nikolay Novi Sofiiski?, buildings of the Synodal Palace, the Central Mineral Baths, and the Higher Theological School at the Holy Synod, built and decorated between 1900 and 1922. They are the works of the architects Friedrich Gr?nanger, Yurdan Milanov and Petko Momchilov. The accent of the research is the ceramic decoration of the facades of the Central Mineral Baths in Sofia, by the project of Haralampi Tachev. The details of the types of ornaments are presented and analysed. The graphic designs for the restoration of the missing elements were considered. The impact of colour in the design of the facades is analysed. The peculiarities in the decoration and the connection of this style with the medieval elements, were examined. The connection of the facade solutions with the Bulgarian historical traditions of the early Middle Ages and Byzantium is explained through examples from Preslav, the capital of the First Bulgarian Kingdom. This way the coloured ceramic tiles of the facades of the Central Mineral Baths are represented as an expression of the Bulgarian medieval tradition in the Secession style in Sofia. The colour facade interpretations of the buildings in Vienna, Paris and Prague of that period are presented for comparison and demonstration of the national differences, decisions and tasks of the Secession style.